ACTANTIAL SCHEMA AND FUNCTIONAL STRUCTURE IN SHORT STORY ṬABLĪYAH MIN AL-SAMĀ’ BY YŪSUF IDRĪS - Mufti Zakwan Thoriq; M Faisol (CMES (Center of Middle Eastern Studies), 2025)
This research analyzes the narrative structure of Yūsuf Idrīs’ short story  Ṭablīyah min al-Samā’ using A. J. Greimas’ structural narratology, with emphasis on the actantial model and functional structure. The story depicts social and spiritual tensions in rural Egypt through the character of Shaykh ʿAlī, who experiences marginalization and existential conflict. Employing a descriptive qualitative design, the research applies close reading and systematic note-taking for data collection. Through Greimas’ actantial scheme comprising six roles: subject, object, sender, receiver, helper, and opponent and a tripartite functional structure (initial situation, transformation, final situation), the analysis identifies five interrelated actantial patterns reflecting the protagonist’s shifting symbolic and social positions. These results highlight the effectiveness of structural narratology in revealing role dynamics, value transformations, and embedded social critique in modern Arabic literature. Furthermore, the study underscores the significance of Greimas’ model for interpreting both narrative and ideological dimensions of texts with strong socio-religious concerns. It concludes by recommending the broader application of structural narratology to modern Arabic works, ideally in combination with ideological or sociological perspectives to deepen textual analysis.